Effect of core training on physical and technical characteristics of novice rhythmic gymnasts / Soheyla Nazari - Soheyla , Nazari (2019)
Enhancing certain characteristics among rhythmic gymnastics (RG) is helpful in the early stages of RG training process. Using descriptive analysis in study 1, the physical & technical characteristics of 100 female Malaysian Rhythmic Gymnasts (6-9 years old) from two gymnastic clubs of Kuala Lumpur were examined. The results of study 1 showed that the mean score of the physical characteristics of the participants in the current study including power, balance, flexibility & strength placed in the range of average compared to the provided norm by Sheerin (2012). For technical characteristics, the results of study 1 showed the essential technical characteristics including jump, balance & pivot skills in this study need to improve since the scores are below 1.00. Gymnastic Federation allow scores of maximum in all level of RG is 1.00 & minimum mark of 0.50. Study 2 (Quasi-experiment), is aimed to assess the effect of the core training program on enhancing the physical & technical characteristics of the Malaysian Rhythmic Gymnasts. From the participants in study 1, 40 rhythmic gymnasts were randomly selected for study 2 which divided in intervention & control groups. Participants in the intervention group received eight weeks of the core training program as the intervention program & control group carried out their normal training without any additional training. The results of Mix within-between ANOVA on the physical variables showed that there was a significant difference in mean of: 1) vertical jump between two groups (F=56.66, p<0.001, η2=0.50) & within three stages of time (F=36.97, p<0.001, η2=0.49); 2) right leg balance between two groups (F=15.93, p<0.001, η2=0.30) & within three stages of time (F=52.26, p<0.001, η2=0.58); 3) left leg balance between two groups (F=4.75, p=0.03, η2=0.11) & within three stages of time (F=2.95, p=0.05, η2=0.07). There was no significant difference in the mean value of sit & reach between two groups (F=0.17, p=0.67) & within three stages of time (F=2.85, p=0.06).Furthermore, The results of Mix within-between ANOVA on the technical variables showed that there was a significant difference in mean of 1) sit-up test between two groups (F=10.15, p<0.001, η2=0.21) & within three stages of time (F=27.70, p<0.001, η2=0.42); 2) scissors jump between two groups (F=14.93, p<0.001, η2=0.28) & within three stages of time (F=33.69, p<0.001, η2=0.47); 3) right leg balance between two groups (F=18.74, p<0.001, η2=0.33) & within three stages of time (F=36.97, p<0.001, η2=0.49); 4) st& erect on toes test between two groups (F=8.13, p<0.001, η2=0.18) & within three stages of time (F=9.11, p<0.001, η2=0.19), 5) pivot passé scores between two groups (F=10.82, p<0.001, η2=0.22), within three stages of time (F=11.64, p<0.001, η2=0.23). Overall, the results of the study showed the intervention program can be introduced as an effective program for improving the physical & technical characteristics of the Malaysian Rhythmic Gymnasts. The findings of the study can be used by Malaysian gymnastics coaches & gymnastics trainers to design & implement a core training program to improve the performance of Malaysian Rhythmic Gymnasts.